Optimalisasi Pembelajaran Norma Pancasila dengan Media Video Animasi Pada Siswa Kelas IV - Nisa, Sarah; Yunita Rahma Pratiwi, Emy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of animated video media on the learning outcomes grade IV on the material of Pancasila norms. The background the low learning outcomes of students due to uninteresting learning methods. This research applied quantitative methods with pre-experiment. The subjects of this study IV grade students. The study employed a pre-test and post-test. Data were analyzed using paired sample t-test statistical test to compare intruments test scores. Finding indicated a notable rise in student’s learning achievements. The normality test results are normally distributed. The paired sample t-test showed an increase in the average score from 49.69 to 86.56 with a difference of 36.87. This finding shows animated video media usage positively and significanly impact studenst learning. Therefore, this study concludes that animated video media is effective improving learning outcomes on Pancasila norms material.